ORGANIZATIONAL CITIZENSHIP BEHAVIOR TEACHERS IN INDONESIA - Syafaat Ariful Huda (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2019)
Purpose: In this study, we investigated the effects of organizational justice and trust directed at the organization as a whole on OCB. Also investigated were the influence between organizational justice and OCB, and the influence between trust and OCB. Design/Methodology/Approach: From a sample of 273 teachers from 305 Private Junior High Schools in Tangerang District, we tested the hypothesized model using structural equation models. Findings: The main findings are as follows: Findings show that organizational justice and trust have a positive effect on teacher’s OCB and OCB is also positively related to trust. Originality/value: The results of the study show that teachers could be engaged in organizational citizenship behavior when they perceive fairness of the equality, needs, rights of opinion, transparency, neutrality and acknowledging the same position of the organizational process.